An Investigation of the Relationship between Corporate Social Responsibility and Corporate Financial Performance in Egypt: The Mediating Role of Information Asymmetry - Nancy Mohamed; Ahmed Rashed (STIE Malangkucecwara, 2021)
The aim of this paper is to investigate the impact of corporate social responsibility (CSR) on corporate financial performance (CFP) through information asymmetry (IA) as a mediator. The study involved the whole sectors in the listed companies on Egx100 excluding Financial sectors (banks and financial services) from 2013-2017 using smart PLS (Partial Least Square). CSR is measured using CSR index, while Share turnover ratio is used to measure IA. CFP is divided into three indicators: ROA, ROE and ROS. The Structural model assessment reveals that CSR has a positive and significant effect on CFP. This means that those listed companies engaged in CSR activities achieved better financial performance than non- CRS companies. The CSR proved to have a negative and significant effect on the IA. This shows that CSR activities lead to decreased IA. Finally, this research found that CSR activities will improve CFP through IA.